Low-Versus Standard-Dose Alteplase for Ischemic Strokes Within 4.5 Hours. Issue 9 (September 2015) - Kim, Beom Joon; Han, Moon-Ku; Park, Tai Hwan; Park, Sang-Soon; Lee, Kyung Bok; Lee, Byung-Chul; Yu, Kyung-Ho; Oh, Mi Sun; Cha, Jae Kwan; Kim, Dae-Hyun; Lee, Jun; Lee, Soo Joo; et al.
<x xml:space="preserve">Abstract</x> Background and Purpose— The low-dose (0.6 mg/kg) alteplase strategy to treat acute ischemic stroke patients became widespread in East Asian countries, without rigorous testing against standard-dose (0.9 mg/kg) alteplase treatment. Our aim was to investigate the comparative effectiveness and safety of the low-dose versus standard-dose intravenous alteplase strategy. Methods— A total of 1526 acute ischemic stroke patients who qualified for intravenous alteplase and treated within 4.5 hours were identified from a prospective, multicenter, and nationwide stroke registry database. Primary outcomes were a modified Rankin scale score of 0 to 1 at 3 months after stroke and occurrence of symptomatic hemorrhagic transformation. Inverse probability of low-dose alteplase weighting by propensity scores was used to remove baseline imbalances between the 2 groups, and variation among centers were also accounted using generalized linear mixed models with a random intercept. Results— Low-dose intravenous alteplase was given to 450 patients (29.5%) and standard-dose intravenous alteplase to 1076 patients (70.5%). Low-dose alteplase treatment was comparable to standard-dose therapy according to the following adjusted outcomes and odds ratios (95% confidence intervals): modified Rankin scale score 0 to 1 at 3 months and 0.95 (0.68–1.32); modified Rankin scale 0 to 2 at 3 months and 0.84 (0.62–1.15); symptomatic hemorrhagic transformation and 1.05 (0.65–1.70); and 3-month mortality and 0.54 (0.35–0.83). The associations were unchanged when the analysis was limited to those without endovascular recanalization. Conclusions— The low-dose alteplase strategy was comparable to the standard-dose treatment in terms of the effectiveness and safety.